Cystic echinococcosis in slaughtered animals in municipal abattoirs in the province of Andahuaylas, Peru - Peña Alvites, Yoel (2022)
The aim of this study was to evaluate the epidemiological factors and economic loss due to cystic echinococcosis (CE) in animals slaughtered in three abattoirs in Andahuaylas (Apurímac, Peru). The study was carried out between October and December 2016 in the municipal abattoirs of the districts of Talavera, Andahuaylas and San Jerónimo. In addition, a retrospective study was carried out, retrieving information from the records of the Epidemiological Format of Diseases Detected in Benefit Centres, corresponding to the years 2011-2016. Between October and December 2016, the percentage of CE infection was 25.7% (95% CI = 24.7-26.7), with the highest percentages in the Andahuaylas abattoir and in the swine species (p˂0.05). The percentage of infection in the 2011-2016 period was 30% (95% CI = 29.8-30.2), with higher frequencies in 2015 and 2016, and in the Talavera abbatoir (p˂0.05). The economic loss during the six years due to the seizure of viscera was USD 155,650.